Circumventing the "true threat" and "viewpoint" protection tests to deal with persistent campus hate speech. Issue 1 (2nd January 2020) - Smith, Craig R.
ABSTRACT: This essay suggests using harassment law as a mechanism for remedying defects in "true threat" and "viewpoint protection" language which places an undue burden of proof on those trying to quell hate speech on campuses. The essay reviews noted failures and their causes in "true threat" and "viewpoint protection" rulings. Currently, the First Amendment of the Constitution protects freedom of expression unless it presents "a clear and present danger, " is treasonous, obscene, libelous or slanderous. The initial "clear and present danger" standard laid out by Justice Holmes in the Schenck decision has been refined in several cases to create an even heavier burden of proof. Currently, based particularly on the Brandenburg v. Ohio and Virginia v. Black rulings, to be prosecutable, speech must be a "true threat, " which means person-specific, imminent, and possible. However, the Supreme Court has also protected hate speech by defining it as "viewpoint" in such case as Indiana v. Hess, Snyder v. Phelps, and Matal v. Tam . This essay concludes by exploring ways to circumvent the "true threat" and "viewpoint" standards by relying on harassment rulings and extending these precedents from the workplace to campus learning environments.